2022
DOI: 10.18805/lr-4926
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Potassium and Zinc on Growth, Yield, Quality and Economics of Green Gram (Vigna radiata L.) under Semi-arid Region of South-west Haryana

Abstract: Background: Pulses are having a number of constraints in their production as compared to their potential in India. Green gram is an important pulse crop of the country after chickpea and pigeonpea lacks optimum fertilizer management, which leads in reduced growth and yield. The current study aimed to study the effects of different levels of potassium and zinc application on growth, yield attributes, yield and quality of green gram. Methods: The field study was conducted during Kharif 2018 at Regional Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The physiological capability of plants to translocate more food from source to sink is measured by the harvest index [43]. These results are in accordance with those of [44], who noted that boron foliar spray produced a maximum harvest index. Similar, results were also reported by Anjum et al [7], who observed an increase in harvest index due to boron foliar application on maize.…”
Section: Foliar Boron (%)supporting
confidence: 87%
“…The physiological capability of plants to translocate more food from source to sink is measured by the harvest index [43]. These results are in accordance with those of [44], who noted that boron foliar spray produced a maximum harvest index. Similar, results were also reported by Anjum et al [7], who observed an increase in harvest index due to boron foliar application on maize.…”
Section: Foliar Boron (%)supporting
confidence: 87%